Transcatheter Closure of Perimembranous Ventricular Septal Defects Using Different Generations of Amplatzer Devices: Multicenter Experience - Roberto Mijangos-Vázquez; Amal El-Sisi; Juan P. Sandoval Jones; José A. García-Montes; Rogelio Hernández-Reyes; Rodina Sobhy; Antoine Abdelmassih; Mohammed M. Soliman; Safaa Ali; Tatiana Molina-Sánchez; Carlos Zabal (Journal of Interventional Cardiology)
Objectives. To demonstrate safety and efficacy of using different generations of softer Amplatzer™ devices for ventricular septal defect (VSD) closure to avoid serious complications at follow-up. Background. Transcatheter closure of perimembranous ventricular septal defects (PmVSD) is a well-established procedure; however, it is associated with unacceptable incidence of complete heart block. Great advantages have been achieved by using softer devices for VSD transcatheter closure. The first and second generation of Amplatzer™ occluders (AVP II, ADO, and ADO II) seem to offer a safe and attractive alternative for this procedure. These devices can be delivered using either an arterial (retrograde) or venous (prograde) approach. Methods and Results. Patients with congenital PmVSD who underwent transcatheter closure using ADO, ADO II, and AVP II devices were included. Primary end point was to determine efficacy and safety of these generations of devices and to determine the incidence of complications at follow-up (complete AV block and aortic/tricuspid/mitral regurgitation). One hundred and nineteen patients underwent VSD closure at a median age of 5 years (8 months–54 years). During the catheterization, there were only minor complications and at follow-up of 36 ± 25.7 months (up to 99 months), the closure rate was high of 98.3% and freedom from AV block was 100%. Conclusions. The use of softer Amplatzer™ devices is a good alternative to achieve PmVSD closure safely with no risk of AVB during the procedure or at midterm follow-up.